2018
DOI: 10.1016/j.pvr.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HPV 6, 11, 16 and 18 and correlates of exposure in unvaccinated women aged 16–64 years in Puerto Rico

Abstract: BackgroundTo understand risk factors for HPV exposure in Puerto Rican women, we evaluated HPV 6, 11, 16, and 18 serology in women aged living in the San Juan metropolitan area.MethodsAs part of a cross-sectional study, a population-based sample of 524 HPV unvaccinated Hispanic women ages 16–64 years completed face-to-face and computer assisted interviews and provided blood and self-collected anal and cervical specimens. Serology used multiplex virus-like particle based-IgG ELISA and HPV DNA was detected with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Immunological tests, extended to SA and VI sera, failed to show any differences in prevalence between groups, although a higher titer was found in SA compared to VI women. Our data are in agreement with seroprevalence results reported earlier [ 95 , 96 ], indicating that HPV16 infects humans, including pregnant females, at a high rate. Since all the DNA samples in our study from SA chorionic villi/PBMC were HPV16-negative, the involvement of HPV in SA is unlikely.…”
Section: Discussionsupporting
confidence: 93%
“…Immunological tests, extended to SA and VI sera, failed to show any differences in prevalence between groups, although a higher titer was found in SA compared to VI women. Our data are in agreement with seroprevalence results reported earlier [ 95 , 96 ], indicating that HPV16 infects humans, including pregnant females, at a high rate. Since all the DNA samples in our study from SA chorionic villi/PBMC were HPV16-negative, the involvement of HPV in SA is unlikely.…”
Section: Discussionsupporting
confidence: 93%
“…Barbados [99], Belize [100,109], Curacao [37], Dominican Republic [39,77], Guyana [73,110], Haiti [46,81,111,112], Netherlands Antilles [113], Puerto Rico [64,65,84,86,89,90,114], Suriname [23,67], Trinidad and Tobago [115], US Virgin Islands [116] In tandem with the utilization of vaccination, efficiency in CvC screening leading to early detection of cytological abnormalities was identified to be imperative to furtive treatment and survival. Belize and Haiti offer all four screening methods mentioned in Table 8 to facilitate the varied needs of their population.…”
Section: Controlmentioning
confidence: 99%
“…Hormonal contraception was said to act as “an enhancer of the neoplastic growth” of cervical carcinoma. The estrogen present in the contraception was stated to bind with the specific DNA that controls the transcription regulatory regions on the HPV genome [ 77 ]. This effect was said to increase with parity.…”
Section: Reviewmentioning
confidence: 99%
“…High-risk types of human papillomavirus (HPV) are thought to be responsible for more than 90% of anal and cervical cancers, about 70% of vaginal, vulvar, and cancers of the oropharynx, and more than 60% of penile cancers [1]. Puerto Rico (PR), a United States (US) territory, have documented the burden of HPV infection and HPV-related cancers in this population [2][3][4]. Studies conducted has reported an increased risk of cervical cancer in this population (compared to mainland US), multiple barriers to cervical cancer screening [5,6], low awareness of HPV and the HPV vaccine [7], increasing trends of anal cancer [8,9] and a higher burden in the incidence and mortality from penile cancer in Puerto Rican men compared with other racial/ethnic groups in the US [10].…”
Section: Introductionmentioning
confidence: 99%